Medio-lateral entry pin versus lateral entry pin for displaced pediatric supracondylar fractures: A comparative, prospective study - Kandel, Manoj; Gupta, Hemant Kumar; Hamal, Rajkumar Ravi; Mishra, Amit Ranjan; Shrestha, Rahul; Ranjan, Abhisek; Shrestha, Robin (Journal of College of Medical Sciences-Nepal, 2016)
Background & Objectives: Supracondylar fracture is one of the commonest fractures in children. Although the technique of pinning is controversial, percutaneous medio-lateral entry pinning is theoretically considered more stable biomechanical construct. The drawback of this method is injury to ulnar nerve which is not encountered in only lateral entry pinning. Materials & Methods: This was a prospective, comparative and observational study done in 60 patients which was alternately divided into two groups. The first group (A) underwent medio-lateral entry pinning and the second group (B) underwent lateral entry pinning. They were followed for 24 weeks and the outcome was assessed using Flynn’s criteria. Results: At twenty-four weeks, the mean loss of range of motion of elbow in medio-lateral pinning group was 3.70 degrees (SD±1.93) and that in lateral pinning group was 4.23 degrees (SD ±1.38). The mean loss in carrying angle at twenty-four weeks in medio-lateral group was 2.93 degrees (SD±2.19) and that in lateral group was 4.17 (SD±2.24). There were 2 (6.67%) cases of iatrogenic ulnar nerve injury in medio-lateral pinning group. Out of thirty patients, in medio-lateral pinning group, 25 had excellent results, 5 had good results and none had fair or poor results. While out of 30 patients in lateral pinning group, 23 had excellent results, 7 had good results and none had fair or poor results. Conclusion: There is no significant difference in outcome in terms of loss of carrying angle and range of motion between the medio-lateral pinning group and the lateral pinning group at the end of 6 months. Journal of College of Medical Sciences-Nepal, Vol.11(4) 2015: 28-31